CONCEPTUAL MODEL OF MENTAL HEALTH AND FAMILY DISRUPTION AS MEDIATING VARIABLES TO ENHANCE THE ROLE OF TIME FLEXIBILITY ON EMPLOYEE PERFORMANCE - Nikmah, Uliyatun (STIE PGRI Dewantara Jombang, 2024)
The transition to flexible work arrangements during the Covid-19 pandemic has changed employees work dynamics, influencing their well-being, family roles, and job performance. This research investigates the relationship between flextime and employees' performance through the mediating roles of mental health and family interference with work. Using the PLS-SEM approach, data collected from 413 employees in Indonesia working under the flexible work arrangement during the pandemic are analyzed. Results indicated that flextime has a positive effect on mental health and family interference with work. Moreover, enhanced mental health can improve task performance, while family interference with work negatively affects task performance. Additionally, the results show that flextime has an indirect impact on employee task performance through the mediation of mental health and work-family conflict. Given the evolving post-pandemic environment, companies may respond by creating flexible work policies that balance employees' personal and professional obligations.